The Effect of Leadership Style on Employee Loyalty with Organizational Climate as a Moderating Variable - Junita Risa Megawati; Haryono Umar (International Journal of Scientific Multidisciplinary Research, 2023)
This study aims to examine and analyze the effect of transformational and transactional leadership styles on employee loyalty, and the effect of organizational climate moderates transformational and transactional leadership styles on employee loyalty. The research method used ex post-facto with 253 samples from employees of PNM Mekaar Ltd. Region Probolinggo business unit. The results show that transformational and transactional leadership styles have a positive effect on employee loyalty, organizational climate has a positive effect on moderating transformational leadership styles and a negative effect on moderating transactional leadership styles